Cardiac time intervals predict major adverse cardiovascular events in individuals with type 1 diabetes without known heart disease. (25th November 2020) - Brainin, P; Lassen, M.C.H; Joergensen, P.G; Biering-Soerensen, T; Andersen, H.U; Rossing, P; Jensen, M.T
Abstract: Background: Cardiac time intervals, and in particular the myocardial performance index (MPI) which combines systolic and diastolic function, are associated with cardiovascular prognosis in various populations. We aimed to investigate if cardiac time intervals offer prognostic information on cardiovascular risk in individuals with type 1 diabetes (T1DM). Methods: We prospectively included 1, 088 individuals with T1DM without known heart disease (mean age 50±15 years; 53% male; duration of diabetes 26±15 years; 30% had albuminuria). All enrolled individuals underwent an echocardiographic examination with assessment of cardiac time intervals by color Tissue Doppler imaging M-mode. We evaluated the isovolumetric relaxation and contraction time (IVRT; IVCT) and ejection time (ET). The MPI was calculated as [(IVRT+IVCT)/ET]. In Cox proportional hazards models, we assessed major adverse cardiovascular events (MACE), a composite of incident heart failure or hospitalization for acute coronary syndrome or PCI/CABG. Multivariable models were adjusted for clinical information, pharmacotherapy and echocardiographic parameters. Results: During the median follow-up time of 6 years [IQR 6, 7 years], 106 (10%) experienced MACE. In adjusted survival analyses the IVRT (HR: 1.13 per 10ms increase [1.01 to 1.26], P=0.026) and MPI (HR: 1.03 per 1 unit increase [1.01 to 1.04], P=0.005) were associated with MACE. Overall, the association between IVCT and outcome was borderline significant (HR: 1.15 per 10ms increase [0.97 to 1.36], P=0.10) while there was no association for ET (HR: 0.97 per 10ms increase [0.89 to 1.05], P=0.43). Sex modified the association for IVCT (P interaction<0.05) such that IVCT (HR: 1.23 per 10ms increase [1.02 to 1.49], P=0.027) and MPI (HR 1.03 per 1 unit increase [1.01 to 1.05], P=0.005; Figure) were associated with MACE in women but not in men. Conclusion: Cardiac time intervals are positively associated with MACE in T1D without known heart disease. Furthermore, the association is modified by sex in that the IVCT and MPI provide independent and prognostic information on the risk of future cardiovascular events particularly in female individuals while not significant in men. These findings suggest sex differences in myocardial impairment related to T1D. Funding Acknowledgement: Type of funding source: None